Kegiatan Organisasi IPNU-IPPNU dalam Membentuk Karakter Peserta Didik Kelas IX SMP Ma’arif Kalibawang Kabupaten Wonosobo Tahun Pelajaran 2024/2025 - Ida Hidayatu Solehah; Ngarifin Shidiq; Salis Irvan Fuadi (Reflection : Islamic Education Journal, 2025)
The IPNU-IPPNU organization has an important role in character building of students at SMP Ma'arif Kalibawang, Wonosobo Regency in 2024/2025. This study aims to describe and analyze how the organization's activities are able to internalize character values ​​such as religiosity, responsibility, discipline, leadership, and cooperation through various activities based on direct experience and real-life practices. The method used is descriptive qualitative field research, with data collection techniques through observation, interviews, and documentation. The data obtained were analyzed using the Miles, Huberman, and Saldana analysis models. The results of the study indicate that the active involvement of students in the IPNU-IPPNU organization significantly improves aspects of character, soft skills, and student discipline, and equips them to become a responsible, religious, and competitive young generation in accordance with the paradigm of experience-based character education.